Short-stay thyroid surgery for older patients: is it safe? - Kalezić, Marko; Živić, Rastko; Djukić, Vladimir; Milanović, Miljan; Ostojić, Milkica; Rančić, Nemanja; Vekić, Berislav (Vojnosanitetski pregled, 2023)
Background/Aim. The incidence of nodular thyroid disease increases significantly with age as well as the incidence and aggressiveness of thyroid cancers. The aim of the study was to determine whether thyroid surgery for geriatric patients is safe in a short hospital stay surgery setting. Methods. In this retrospective study, medical histories of all operated geriatric patients (65 years and older), in whom a total thyroidectomy (TT) or hemithyroidectomy (HT) was performed from January 2012 to December 2018, were analyzed. A total of 976 patients were operated on for thyroid diseases in the mentioned period, out of which 247 geriatric patients fulfilled the inclusion criteria. Patients with thyroid reoperations and simultaneous neck lymph node dissections were excluded from the study. The geriatric patients were divided into two groups: the HT group (33 patients) and the TT group (214 patients). Each of these two geriatric groups, HT and TT, had two additional paired control groups. Control group I consisted of younger subjects from 20–44 years, and control group II included middle-aged subjects from 45–64 years. Results. All three TT groups – geriatric, control I, and control II, had 214 patients each, and all three HT groups had 33 patients each. In all three HT groups, the average hospital stay was 24 hrs, while in the TT geriatric group, 150 (70.1%) of 214 patients spent 24 hrs at the hospital. In the geriatric population, the incidence of neck swelling and increased drainage output were higher compared to both control groups, and thus the need for longer hospitalizations. When the age was compared, it was shown that subjects with each subsequent year of intervention had a 22% lower chance of developing complications, and regarding the pathohistological finding, benign thyroid hyperplasia was less likely to develop complications compared to malignant hyperplasia. Conclusion. According to the study, TT can be safely performed within the concept of a short hospital stay in patients under 65 years, while in the elderly, hospitalization days may be extended due to more frequent surgical and nonsurgical complications. Speaking of HT, the short hospital stay is safe for all age groups.